Why Women Are Averse to Facility Delivery in Northwest Nigeria: A Qualitative Inquiry - *Ismail TUKUR; Chan CHEEKHOON; Tin TINSU; Tukur MUHAMMED- BABA; Munir'deen ADEREMI IJAIYA (Tehran University of Medical Sciences, 2016)
Background: In many sub-Saharan African countries the rate of antenatal care (ANC) has been increased but skilled birth attendance rate is still low. The objective of this study was to evaluate the reasons why women prefer home delivery when facility based delivery is available at minimal cost. Methods: This study was conducted in Northwest Nigeria using a qualitative method (phenomenology) among five categories of women in April - May 2013. This study investigated different categories of women (those that never attend ANC nor deliver in the facility, those that attend ANC but delivered at home and those that delivered once in the facility but fail to return in subsequent deliveries, the in-laws and facilities staff). Results: Through focus group discussions and In-depth interviews several reasons why women are averse to hospital deliveries were identified. Women reported ignorance, abuse, illiteracy, and poverty, and low esteem, poor attitude of health workers, few working hours and some integrated health services like preventing mother to child transmission of HIV testing as deterrents, while cheap and accessible services were reasons for preference to traditional birth attendants. Conclusions: The findings highlighted important entrenched barriers to facility deliveries among women, which is basically socio-cultural and economic. Therefore emphasis must be given to health education program to ensure comprehensive and target specific messages that will address individual needs of the groups.   Keywords: Barriers, Hospital delivery, Qualitative inquiry, Northwest Nigeria